2020
DOI: 10.1161/strokeaha.120.029245
|View full text |Cite
|
Sign up to set email alerts
|

Higher Doses Improve Walking Recovery During Stroke Inpatient Rehabilitation

Abstract: Background and Purpose: We investigated the effect of higher therapeutic exercise doses on walking during inpatient rehabilitation, typically commencing 1 to 4 weeks poststroke. Methods: This phase II, blinded-assessor, randomized controlled trial recruited from 6 Canadian inpatient rehabilitation units, between 2014 and 2018. Subjects (n=75; 25/group) were randomized into: control (usual care) physical therapy: typically, 1 hour, 5 days/week; Determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 24 publications
2
84
0
Order By: Relevance
“…Though the mean step count per physical therapy session in the Exoskeleton group was nearly double that of the Usual Care group, 592 steps is low relative to other walking intervention studies. Klassen et al conducted a randomized controlled trial comparing one or two daily high-dose walking-focused physical therapy sessions to standard physical therapy care during subacute stroke rehabilitation; participants receiving either higher-dose therapy regimens achieved greater 6MWT distances at follow-up than participants receiving standard care [ 56 ]. In that study, participants in standard physical therapy took an average of 580 steps per session, whereas the higher dose groups achieved 2169 and 4747 steps per session [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the mean step count per physical therapy session in the Exoskeleton group was nearly double that of the Usual Care group, 592 steps is low relative to other walking intervention studies. Klassen et al conducted a randomized controlled trial comparing one or two daily high-dose walking-focused physical therapy sessions to standard physical therapy care during subacute stroke rehabilitation; participants receiving either higher-dose therapy regimens achieved greater 6MWT distances at follow-up than participants receiving standard care [ 56 ]. In that study, participants in standard physical therapy took an average of 580 steps per session, whereas the higher dose groups achieved 2169 and 4747 steps per session [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Klassen et al conducted a randomized controlled trial comparing one or two daily high-dose walking-focused physical therapy sessions to standard physical therapy care during subacute stroke rehabilitation; participants receiving either higher-dose therapy regimens achieved greater 6MWT distances at follow-up than participants receiving standard care [ 56 ]. In that study, participants in standard physical therapy took an average of 580 steps per session, whereas the higher dose groups achieved 2169 and 4747 steps per session [ 56 ]. Participants in a trial conducted by Hornby et al took 2358 steps per intervention session, and demonstrated greater gait speed and 6MWT improvements than participants in the control group [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the number of steps in the walking non-independence group was 1970 steps/day (IQR, 1334.8-3105.3 steps/day) for FAC 2 and 2646 steps/day (IQR, 1669-3521 steps/day) for FAC 3. Klassen et al reported that the number of steps during a physical therapy session was 580 (SD, 440) for usual care physical therapy, 2169 (SD, 1106) for more than double the intensity of the control, and 4747 (SD, 2083) for more than quadruple the intensity of the control, and walking recovery was improved in the higher dose group [29]. Patients with FAC 2.3 in our study did not reach the values of the previous study; however there is still a possibility of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of specific exercise prescription guidelines, rehabilitation therapists provide low exercise doses, despite evidence that higher intensity exercise improves neural and functional recovery. 1,3 When general targets are given to research therapists, our recent study shows more than double the steps and aerobic minutes can be achieved vs usual care and translates to improved long-term walking outcomes. 1 Yet, safety concerns keep some therapists from delivering higher exercise intensity 4 since the subacute stroke period is a time of higher risk for cardiac complications.…”
Section: Introductionmentioning
confidence: 99%